EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS DIGITAL DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR: SEBUAH LITERATURE REVIEW - Khairunnisa, Mutia; Naswanal Saputri; Rahma Fadhila; Ari Suriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to comprehensively analyze the effectiveness of digital-based learning media in improving elementary school students' mathematics learning outcomes based on a review of literature published from 2020 to 2025. The method used is a systematic literature review (SLR) with the PRISMA approach. The selection process was conducted on 87 initial articles from Google Scholar, DOAJ, and Portal Garuda databases, resulting in 25 final articles that met the inclusion criteria. The analysis results show that digital media such as Quizizz, Wordwall, Canva, and YouTube Education are effective in improving elementary school students' mathematics learning outcomes with an average increase of 15%–32%. The highest effectiveness was found in the use of Wordwall for fraction material in grade IV with a blended learning model. Game-based media (Quizizz, Wordwall) were superior for procedural-computational material, while visual media (Canva, YouTube) were more effective for geometry concept learning. Three main recurring obstacles were limited student devices, heterogeneity of teachers' digital competence, and internet instability. This study concludes that the effectiveness of digital media is highly dependent on learning design suitability, material characteristics, and the teacher's facilitation role.